The experiences of female bisexual student-athletes in China: an interpretative phenomenological analysis - Xiang, Meng; Soh, Kim Geok; Xu, Yingying; Ahrari, Seyedali; Zakaria, Noor Syamilah (Frontiers Media, 2023)
Introduction: Many scholars have explored the participation of LGBTQ individuals in sports. However, these studies have either categorized homosexuality and bisexuality together or focused only on lesbian, gay, or transgender individuals. There is a lack of research in the literature on bisexual individuals’ sports participation and an even more significant lack of Asia perspectives. Therefore, this qualitative study is aimed to explore the experiences of female bisexual student-athletes in China.